Molecular modeling of retinoschisin with functional analysis of pathogenic mutations from human X-linked retinoschisis - Sergeev, Y.V.; Caruso, R.C.; Meltzer, M.R.; Smaoui, N.; MacDonald, I.M.; Sieving, P.A. (Human molecular genetics, 2010)
Gene mutations that encode retinoschisin (RS1) cause X-linked retinoschisis (XLRS), a form of juvenile macular and retinal degeneration that affects males. RS1 is an adhesive protein which is proposed to preserve the structural and functional integrity of the retina, but there is very little evidence of the mechanism by which protein changes are related to XLRS disease. Here, we report molecular modeling of the RS1 protein and consider perturbations caused by mutations found in human XLRS subjects. In 60 XLRS patients who share 27 missense mutations, we then evaluated possible correlations of the molecular modeling with retinal function as determined by the electroretinogram (ERG) a- and b-waves. The b/a-wave ratio reflects visual-signal transfer in retina. We sorted the ERG b/a-ratios by patient age and by the mutation impact on protein structure. The majority of RS1 mutations caused minimal structure perturbation and targeted the protein surface. These patients' b/a-ratios were similar across younger and older subjects. Maximum structural perturbations from either the removal or insertion of cysteine residues or changes in the hydrophobic core were associated with greater difference in the b/a-ratio with age, with a significantly smaller ratio at younger ages, analogous to the ERG changes with age observed in mice with no RS1-protein expression due to a recombinant RS1-knockout gene. The molecular modeling suggests an association between the predicted structural alteration and/or damage to retinoschisin and the severity of XLRS as measured by the ERG analogous to the RS1-knockout mouse.